2009
DOI: 10.1161/strokeaha.109.559898
|View full text |Cite
|
Sign up to set email alerts
|

Silent Cerebral Infarcts in Patients With Pulmonary Embolism and a Patent Foramen Ovale

Abstract: Background and Purpose-Pulmonary embolism is thought to be associated with a small but definite risk of paradoxical embolism in patients with a patent foramen ovale (PFO). Although neurological complications are infrequent, the incidence of clinically silent brain infarction is unknown. We assessed the rate of clinically apparent and silent cerebral embolism in patients with pulmonary embolism in relation to the presence or not of a PFO. Methods-We used diffusion-weighted MRI in patients hospitalized for a pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
1
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 25 publications
1
36
1
11
Order By: Relevance
“…A recent study, which considered PE patients classified as intermediate-risk, revealed a PFO prevalence of 17.7 % [8]. On the contrary, a lower percentage have been found from Clergeau et al in PE patients classified as low-risk PE [9]. Nowadays, despite seems that the prevalence of PFO increases with the severity of PE, due to the absence of definitive results, the real prevalence of PFO among the different PE risk groups remains matter of speculation.…”
Section: Evidence From the Literaturementioning
confidence: 85%
“…A recent study, which considered PE patients classified as intermediate-risk, revealed a PFO prevalence of 17.7 % [8]. On the contrary, a lower percentage have been found from Clergeau et al in PE patients classified as low-risk PE [9]. Nowadays, despite seems that the prevalence of PFO increases with the severity of PE, due to the absence of definitive results, the real prevalence of PFO among the different PE risk groups remains matter of speculation.…”
Section: Evidence From the Literaturementioning
confidence: 85%
“…That PFO may enhance the risk of getting brain emboli has been further elegantly shown by a recent prospective study that identified, by logistic regression analysis, PFO was found to be an independent predictor of silent brain infarction with an OR of 34.9 (95% CI 31-394.3, P = 0.004) [7].…”
Section: -7mentioning
confidence: 90%
“…They came to the conclusion that PFO may represent an incidental finding in 33-48% of cryptogenic strokes when in isolation, but only in 11% when associated with bulging of the interatrial wall (so called atrial septal aneurism -ASA). These figures drop to 20% and 9%, respectively, in patients less than 55 years old [5].Similarly, a prospective study conducted in France on the risk of recurrence in young patients with cryptogenic stroke [6] showed that, compared with patents with no atrial septal abnormalities, the PFO-ASA association conveyed a 4-fold risk of relapse (hazard ratio 4.17, 95% CI 1.47-11.84).That PFO may enhance the risk of getting brain emboli has been further elegantly shown by a recent prospective study that identified, by logistic regression analysis, PFO was found to be an independent predictor of silent brain infarction with an OR of 34.9 (95% CI 31-394.3, P = 0.004) [7].The difficulty in identifying those with truly cryptogenic stroke amongst aged patients (due to the frequent cooccurrence of vascular risk factors) probably explains why PFO was only marginally associated with stroke in patients aged over 55 years in older studies [1]. Recent evidence, however, strongly suggests that PFO is over-represented in cryptogenic strokes irrespective of the age of occurrence [4].…”
mentioning
confidence: 95%
“…This is significantly more common than in patients without a PFO, which was reported at 2% (n = 1/45, p = 0.003) [9]. Numerous retrospective, casecontrol studies have also shown a higher prevalence of PFO in patients with cryptogenic stroke.…”
Section: Patent Foramen Ovale and Cryptogenic Strokementioning
confidence: 95%